Impact of COVID‐19 on Prenatal Diagnosis and Surgical Outcomes of Congenital Heart Disease: Fetal Heart Society and Society of Thoracic Surgeons Collaborative Study - Bhawna Arya; Miza Salim Hammoud; Andrew J. Toth; Joyce Woo; Matthew Campbell; Angira Patel; Lindsay A. Edwards; Lindsay Freud; Rupali Gandhi; Anita Krishnan; Shabnam Peyvandi; Nelangi Pinto; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Fetal echocardiography is the mainstay of prenatal diagnosis of congenital heart disease. The COVID‐19 pandemic led to shifts in triage of prenatal services. Our objective was to evaluate the impact of COVID‐19 restrictions on prenatal diagnosis, surgical outcomes, and disparities in neonatal critical congenital heart disease (CCHD) management in the United States during the pandemic's first year. Methods and Results A multi‐institutional retrospective cohort study compared neonatal CCHD outcomes (requiring surgery within 60 days of birth) 1 year prior (prepandemic era) and during the peak pandemic era, supplemented by a Fetal Heart Society survey assessing regional practice changes. Data on prenatal diagnosis, demographics, outcomes, and 2020 state Area Deprivation Index were analyzed using Wilcoxon rank sum and χ2 tests. The survey, completed by 72 fetal cardiologists from 9 US census regions, showed 75% of institutions implemented restrictions by March 2020, affecting triage, referrals, and number of prenatal cardiology visits. Compared with CCHD neonates born prepandemic (n=4637), those born during the pandemic (n=1806) had a higher proportion of prenatal diagnosis (66% versus 63%, P<0.05). There were no significant differences in complications or mortality, but pandemic‐era neonates had longer hospital stays. During the pandemic, CCHD neonates had a more disadvantaged Area Deprivation Index and had surgery at hospitals located in more advantaged regions. Conclusions Although pandemic‐driven care delivery adjustments affected perinatal cardiology referrals and triage, prenatal diagnosis, perioperative outcomes, and survival remained robust. The management of CCHD demonstrates health care resilience, maintaining core prenatal and perioperative care. Regional variations highlight the need for targeted strategies to address disparities during health care crises.